Pharmacoeconomic evaluations of ceftriaxone and cefixime in the surgery department in a tertiary care teaching hospital - Basattikoppalu Puttegowda, Satish Kumar; Dahim, Muhammed; Basaralu Nagarajappa, Ravindra; Anakuzhikkara Thekkuveettiil, Najna Bai (International Journal of Research in Medical Sciences, 2023)
Background: Pharmacoeconomics involves the analysis of the cost of drug therapy in the health systems which will play a significant role in drug product selection for formulary, comparison of alternative therapies pricing a product and evaluating a drug product and expected quality of life improvement. Objective were to assess pharmacoeconomic evaluation and cost minimization analysis of ceftriaxone and cefixime in the surgery department in a tertiary care teaching hospital. Methods: This prospective observational study conducts to pharmacoeconomic evaluation of ceftriaxone and cefixime. It analyses the number of available brands and generic drugs and performs a cost-minimization analysis for these drugs used in the surgery department. Results: The study includes a total of 173 patients, among them 68 patients (39%) were using ceftriaxone, 39 patients (23%) were using cefixime and 66 patients (38%) were using ceftriaxone and cefixime (IV-PO) for various surgery cases. Monocef (₹121.04; 1.04 per day) was the most commonly used ceftriaxone brand, while Gramocef (₹114; 1.38 per day) least and Xone (₹112; 1.38 per day) were the cheapest options. The mean ceftriaxone cost for a vial is 56.67±10.04 and the tablet is 113.33±20.08 per day. Cost minimization analysis shows that most prescribed drugs were costlier than least prescribed drugs. Taxim-O (₹107.72; 1.30 per strip) was the most prescribed cefixime brand and the least Tanfix ( 1.3: ₹107 per strip). The mean of cefixime cost per strip is 107.6±0.28; 1.31 and per day 21.51±0.05; 0.26. There is no major cost difference or price variation in cefixime brands (0.69%). Conclusions: The cheaper drugs should be prescribed to patients rather than the costlier and it should be the duty of healthcare professionals to consider the pharmacoeconomic value of drugs while prescribing the medications.